Description of A New Species of Orb-Weaving Spider of the Genus Cyrtarachne Thorell, 1868 from Bangladesh (Araneae : Araneidae : Cyrtarachninae) (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Taxonomic description of a new species of orb-weaving spider of genus Cyrtarachne Thorell is provided herewith. In this study, species Cyrtarachne kaikobadi n. sp. was identified as new to science. The paper presents an illustrated description of the new species together with brief generic diagnosis and distribution.J. Asiat. Soc. Bangladesh, Sci. 51(1): 115-122, June 2025